1991
DOI: 10.1111/j.1745-4549.1991.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSSITIONAL, NUTRITIONAL and FUNCTIONAL EVALUATION of INTERMEDIATE WHEATGRASS (THINOPYRUM INTERMEDIUM)

Abstract: ‘Oahe’ Intermediate Wheatgrass (IWG) seed was found to have higher levels of protein (20.8%), fat (3.21%), and ash (2.64%) than wheat. the IWG protein is nutritionally limiting in lysine, as is wheat, but has higher levels of all other essential amino acids than wheat. A flour beetle larvae bioassay and chemical trypsin inhibitor and hemagglutinin tests demonstrated the absence of significant amounts of antinutrients. IWG kernels were milled with stone, impact, and roller mills. Stone milling resulted in a flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 4 publications
2
50
0
2
Order By: Relevance
“…Chemical composition of HWF and IWG is shown in Table I. Despite having more protein, it has been reported that perennial grasses are characterized by low gluten content (Becker et al 1991). IWG flour exhibited a significantly (P £ 0.05) lower total starch content compared with both refined and whole wheat flour (46.7, 73.9, and 72%, respectively) and a higher amount of protein (20, 15, and 13.2% for IWG, HWF, and whole wheat flour, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical composition of HWF and IWG is shown in Table I. Despite having more protein, it has been reported that perennial grasses are characterized by low gluten content (Becker et al 1991). IWG flour exhibited a significantly (P £ 0.05) lower total starch content compared with both refined and whole wheat flour (46.7, 73.9, and 72%, respectively) and a higher amount of protein (20, 15, and 13.2% for IWG, HWF, and whole wheat flour, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Although IWG seed protein is nutritionally poor in lysine, as is wheat, it has a higher amount of all other essential amino acids than wheat (Becker et al 1991). Although IWG seed protein is nutritionally poor in lysine, as is wheat, it has a higher amount of all other essential amino acids than wheat (Becker et al 1991).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Wagoner (1990a) described in detail the characteristics that make intermediate wheatgrass a good candidate for domestication as a perennial grain, while noting shortcomings that must be addressed. Becker et al (1991) concluded that its grain has protein quality "superior to the cereal grains now commonly grown", with no significant amounts of antinutrients.…”
Section: Intermediate Wheatgrassmentioning
confidence: 99%
“…Therefore, properties of intermediate wheatgrass grain are expected to be somewhat akin to wheat, but substantial differences are also expected. Efforts to study the chemical properties of intermediate wheatgrass flour in various applications have been completed, and these results are expected to help direct future product development and selection programs aimed at improving grain quality parameters [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%